Slow-Paced Breathing and Autonomic Function in People Post-stroke - Larson, Mia; Chantigian, Daniel P.; Asirvatham-Jeyaraj, Ninitha; Van de Winckel, Ann; Keller-Ross, Manda L. (Frontiers in Physiology, 2020)
Purpose: To determine if acute slow breathing at 6 breaths/min would improve baroreflex sensitivity (BRS) and heart rate variability (HRV) and lower blood pressure (BP) in adults after stroke. Methods: Twelve individuals completed two randomized study visits where they performed a 15-min bout of breathing exercises at 6 breaths/min (slow) and at 12 breaths/minute (control). Continuous BP and heart rate (HR) were measured throughout and BRS, BRS response to elevations in blood pressure (BRSup), BRS response to depressions in blood pressure (BRSdown), and HRV were calculated and analyzed before (pre), during and after (post) breathing exercises. Results: BRS increased from pre to post slow breathing by 10% (p=0.012), where BRSup increased from pre to during slow breathing by 30% (p=0.04). BRSdown increased from pre to post breathing for both breathing conditions (p<0.05). Heart rate (Control: Δ-4±4; Slow: Δ-3±4 beats/min, time, p<0.01) and systolic BP (Control: Δ-0.5±5; Slow: Δ-6.3±8mmHg, time, p<0.01) decreased after both breathing conditions. Total power, low frequency power and standard deviation of normal inter-beat intervals (SDNN) increased during the 6 breaths/minute condition (condition×time, p<0.001), whereas high frequency increased during both breathing conditions (time effect, p=0.009). Conclusions: This study demonstrated that in people post-stroke, slow breathing may increase BRS, particularly BRSup, more than a typical breathing pace, however, mindful, paced-breathing at either a slow or typical breathing rate appears to be beneficial for acutely decreasing SBP and HR and increasing HRV.